Physical properties of particle board from paddy straw, an agricultural waste - Farizul Hafiz, Kasim; Suhardy, Daud; Mohd Nazry, Salleh; Khairuddin, Md Isa; Saiful Azhar, Saad (Universiti Putra Malaysia (UPM) & Institution of Chemical Engineers, Malaysia, 2008)
Organized by Universiti Putra Malaysia (UPM) & Institution of Chemical Engineers, Malaysia, 12th -14th December 2007 at Universiti Putra Malaysia, Serdang, Selangor.